Bacterial taxa and fungal diversity are the key factors determining soil multifunctionality in different cropping systems. (17th September 2021) - Zhang, Jiangzhou; Li, Tengteng; Jia, Jiyu; Zhang, Junling; Zhang, Fusuo
Abstract: Soil microbes in the topsoil have long been the centre of cropping systems, yet the influence of subsoil microbes on soil functions remains elusive. Sustainable crop management will require an in‐depth understanding of interactions of cropping patterns, soil microbials and multifunctionality. This study aimed to explore the relationships between soil microbials and multifunctionality in both topsoil and subsoil of different cropping systems. We did paired samplings from four cash crops and adjacent wheat/ maize rotation system fields at 0–15 cm and 15–30 cm depths on calcareous soils: cotton (C)‐wheat (WC), grape (G)‐wheat (WG), vegetable (V)‐wheat (WV) and watermelon (W)‐wheat (WW). The results showed that soil multifunctionality in topsoil was higher than in subsoil across all soil samples. In topsoil, soil multifunctionality in W was significantly higher than other cash crops, and the highest and lowest values were in the WG and WC, respectively. In the subsoil, soil multifunctionality in the C was significantly lower than other cash crops. Across the wheat fields, soil multifunctionality were significantly higher in WG and WW than in WC and WV. The structural equation model showed that soil organic carbon, bacterial community composition and fungal diversity were positively correlated with soil multifunctionality in both soil depths. Proteobacteria and Bacteroidetes in topsoil were the important drivers, while Firmicutes and Gemmatimonadetes were in the subsoil. Our results suggest that microbes in both topsoil and subsoil should be integrated into agricultural management practices. The alteration of fungal diversity and bacterial community composition may significantly affect soil multifunctionality in intensive agroecosystems.